ANALISIS PENGARUH VARIABEL MAKROEKONOMI TERHADAP RESIKO KREDIT PADA BANK SYARIAH DI INDONESIA - Sucik Lestari; Mufti Arief Arfiansyah (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This study aims to analyze the influence of macroeconomic factors, such as the inflation rate, Bank Indonesia interest rate (BI Rate), and economic growth (GDP), on credit risk, which is measured through Non-Performing Financing (NPF) in Islamic Commercial Banks in Indonesia during the 2020–2024 period. The approach used in this study is quantitative, utilizing secondary data obtained from the financial reports of Islamic banks registered with the Financial Services Authority (OJK), with a sample size of 220 data points. The analysis is conducted using panel data regression with the Random Effect Model (REM), selected through the Chow test, Hausman test, and Lagrange Multiplier test. The results show that inflation, BI Rate, and economic growth have a negative and significant effect on NPF. Therefore, increases in these macroeconomic variables tend to reduce the level of problematic financing in Islamic banking. These findings have important implications for regulators and Islamic banks in formulating risk management policies to maintain financial system stability